Austria : 2012 Article IV Consultation: Staff Report; Informational Annex; Statement by the Staff Representative; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Austria. (IMF Staff Country Reports; Country Report ;, 2012)
Austria has relatively strong macroeconomic fundamentals, but also deep ties with the rest of the euro area. The legacy of an overly ambitious eastward financial sector expansion has created substantial challenges to its policymakers. Policies have been designed to preserve market confidence, increase resilience against future adverse external spillovers, and boost potential growth. The Austrian supervisory authorities have also introduced a set of macroprudential guidelines to strengthen the resilience of the banking sector. However, improvements in the fiscal governance framework have not advanced as expected.